Entangling nuclear spins using photoexcited triplet states - Filidou, V (2012)
Entanglement is one of the most technologically important quantum phenomena and its con-trolled creation brings us a step closer to the realisation of a quantum computer. Hybrid electron and nuclear spin systems which combine long nuclear decoherence times with the high polarisation and rapid processing times of electron spins are considered reliable candidates for the representation of the fundamental building block of a quantum computer, the qubit. In the literature electron spins quite often play the role of a mediator which can access, manipulate and couple states with long coherence times, beneficial for storing quantum information. Despite the fact that an electron spin can be a useful resource for nuclear spin systems, its permanent presence can be a source of decoherence. The use of transient photoexcited electron spins provide an additional advantage and once the operations which involve the electron spin are completed, the electron spin can decay and not interfere further with the evolution of the system. In this thesis we report magnetic resonance experiments and density functional theory calculations for the demonstration of nuclear - nuclear entanglement using photoexcited triplet states. We study homonuclear and heteronuclear fullerene derivatives and we identify in each case the relevant parameters that can lead to high fidelity entangling operations. The hyperfine interaction in a homonuclear system is the key parameter which determines the degree of entanglement between the nucelar spins according to a recent theoretical proposal. We measure and calculate the hyperfine interaction in homonuclear systems with 13C nuclear spins in order to prove the feasibility of this scheme. Further experiments on a fullerene system with two nuclear spins a 31P and a 1H show that entangling operations of high fidelity which involve the demonstration of CNOT gates, are possible within the lifetime of the triplet state.